IMPROVING TEACHER CAPABILITY IN IMPLEMENTING STRENGTHENING CLASS-BASED CHARACTER EDUCATION THROUGH WORKSHOP IN NOMPOREJO STATE PRIMARY SCHOOL - Suratinem Suratinem (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2023)
The not optimal application of character education in learning has an impact on reducing student character. This can be seen in the results of the Student Self-Evaluation (EDS) which show that most teachers have not integrated strengthening character education into learning materials. This requires school principals to carry out new innovations in improving teacher abilities in implementing class-based strengthening character education through workshops. The purpose of this research is to describe how to improve teachers' abilities in implementing classroom-based strengthening character education through workshops at SD Negeri Nomporejo. This research method is in the form of classroom action research. The results of this study indicate that the steps of the workshop through the process of planning, implementing, reflecting and assessing and evaluating have increased success rates. Workshops can improve teachers' abilities in implementing classroom-based strengthening of character education at Nomporejo Kapanewon Galur Public Elementary School for the 2021/2022 Academic Year. This can be seen in the comparison of teachers' abilities in implementing strengthening character education in Pre-Action, Cycle I, and Cycle II. The teacher's ability to apply Strengthening Character Education increased by an average of 67.9% in Pre-Action with category D, increased to 72.35% in Cycle I with category C, increased again to 86.5% in Cycle II with category B.